Legal Responsibility of Skincare Companies for Overclaim-Based Marketing Strategies (Misleading Benefits) - Pitra Regina Sipahutar; Roida Nababan; Sovia F. T Simamora (PT FORMOSA CENDEKIA GLOBAL, 2025)
Overclaim (misleading benefits) often occurs through excessive claims regarding product benefits that are not supported by adequate scientific evidence, thus misleading consumers and creating unfair business competition. Based on Law Number 8 of 1999 concerning Consumer Protection and BPOM regulations, companies can be held accountable based on the principles of strict liability and product liability, which require business actors to provide compensation. In this study, the author will discuss the legal responsibility of skincare companies for the practice of overclaim (misleading benefits) in marketing their products and the legal efforts that can be taken by consumers who are harmed. By using normative legal methods and qualitative approaches, the results of the study show that companies can be held accountable based on the principles of strict liability and product liability in accordance with the Consumer Protection Law (UUPK) and BPOM regulations. Consumers who experience losses can seek dispute resolution through non-litigation channels (mediation, arbitration, or the Consumer Dispute Resolution Agency) or litigation (court). Overclaim, Skincare, Legal Responsibility, Consumer Protection